NOTION, ELEMENTS AND EVALUATION OF HUMAN RESOURCES MANAGMENT IN SPORT - Milorad M. Drobac; Milica Radović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Principal object of the author's research in work is identification of notion, cru- cial elements and evaluation of human resources management in general and apart in sport. From the beginning of usage of term "human resources management", we use foretoken "strategic" that has especially signified meaning. Strategic approach to the exploration of this problem points to the fact that human resources are from particularly significance for all forms of human organization (firms, associations, institutions etc.), regardless are we talking about economy, social activity, politics, science, sport or any other area of human activity. Experience shows that, in our society, we mainly considered human resources management from the aspect of formulation and implementation of strategy in any shape and segment of altogether human activity, but we pay a little interest to the control, or in other words evaluation of human resources performance. What is attained in world rela- tions, on the human resources management plan, admonish and binds that we must ac- cept employees in our environment (it implies sport) as an equal partner in management